Unexpected outcomes from an AI education course among education faculty: Toward making AI accessible with marginalized youth in urban Mexico - Kasun, G. Sue; Liao, Yin-Chan; Margulieux, Lauren Elizabeth; Woodall, Maya (Frontiers in Education, 2024)
The authors explore the intersection of AI and equity in education, presenting a workshop designed for marginalized youth in urban Mexico. This reflective essay stems from their participation in the International Society for Technology in Education’s AI and education course. The lead author, a language education researcher who emphasizes equity in her scholarship, crafted a presentation on AI’s everyday applications for marginalized Mexican youth. Collaborating organically, the co-authors positioned this project as the course’s final collective output, fostering a unique blend of expertise and community engagement. The lead author designed the presentation for an organization with which she has partnered for over a decade, an educational project that supports learning and life skills, rooted in Don Miguel Ruiz’s Four Agreements, for children who live in a community of unofficial housing on the edge of railroad tracks in Cuernavaca, Mexico. The project aimed to bridge the global application of AI to marginalized Mexicans, facilitating a two-hour workshop in Spring 2023. Two additional faculty, technology education researchers, joined the effort to promote computational literacy equitably through culturally relevant pedagogy. They highlight their diverse scholarly backgrounds, positioning themselves as individuals from the margins, and share their motivation for creating a cogent and engaging workshop for the youth. The lead author reports on the unexpectedly rich conversation that unfolded during the workshop, underscoring the potential for AI to be inclusive as society navigates its integration into education.